Wikibrands reinventing your company in a customer-driven marketplace - Moffitt, Sean; Dover, Mike (McGraw-Hill, 2011)
Sean Moffitt and Mike Dover show you how to take advantage of the exciting new models of business and technologies--and enthusiastic online communities--one click at a time. --from publisher description.